A sinfonia da natureza: Charles Darwin e as origens - Dias, Vivian Catarina (2015)
Since childhood Charles Darwin showed an interest for the natural world. In his youth he developed that passion into an object of study travelling around the world onboard of The Beagle. The contact with unique species like the ones found in Galapagos Islands, the fossils discovered in South America, the experiences he lived and a extensive reseach during more than twenty years after his return to England made him think about a common link between the species, that lead him to publish The origin of species in 1859 and The expression of emotions in man and animals in 1872, along with other works and articles on the most diverse subjects, such as Diary of a naturalist around the world. In The origin of species he stated that the species are mutable and linked by the proccess of communion of ascendancy , fruits from the same tree of life. Forging the recreation of human history and its relocation in the natural world, the essays in The expression of emotions in man and animals widened the statement about the evolution of species pointing that humans share emotions and feelings with other species of animals. The implosion of the concept of human initiated with the darwinian facts opened new horizons for sciences such as anthropology to rethink the trajectory of the living beings and the borderlines between culture and animality. Notwithstanding, go beyond frontiers and enrich the critic, scientific, ethic and poetic repertoire is a really dificult task. Despite the relevance of the Darwinian Works, the contact with them is through indirect ways: cartoons, films and fiction, whose contents rarely approach the issue in all its depth